A review of the anglerfish genus Chaunax (Lophiiformes: Chaunacidae) from New Zealand and adjacent waters, with descriptions of four new species - Ho, Hsuan-Ching; Roberts, Clive D.; Stewart, Andrew L. (Zootaxa, 2013)
Species of the anglerfish genus Chaunax Lowe, 1846 from the New Zealand region are taxonomically reviewed with six species recognized and described: Chaunax penicillatus McCulloch; C. nudiventer Ho & Shao, a new record for New Zealand; and four species new to science. Chaunax flavomaculatus sp. nov. distinguished by having its skin covered with a mix of numerous bifurcated and simple spinules, large yellow spots on dorsal surface of fresh specimens, and brownish coloured escal cirri; Chaunax mulleus sp. nov. by having a uniformly pink body with a deep red colour on ventral surfaces of the outer pectoral-fin and pelvic-fin, and lower part of caudal fin; Chaunax reticulatus sp. nov. by having cirri on the dorsal surface of head, and a pale reticulate colour pattern on a greyish background dorsally; and Chaunax russatus sp. nov. by its very wide illicial trough that is usually as wide or wider than the diameter of the pupil, and uniformly deep red body colour with creamy white to fuzzy greyish spots or patches on its dorsal surface. A key to species recognized from the study area is given.